Preoperative imaging and prediction of oesophageal conduit necrosis after oesophagectomy for cancer. Issue 10 (11th May 2017) - Lainas, P.; Fuks, D.; Gaujoux, S.; Machroub, Z.; Fregeville, A.; Perniceni, T.; Mal, F.; Dousset, B.; Gayet, B.
Abstract: Background: Oesophageal conduit necrosis following oesophagectomy is a rare but life‐threatening complication. The present study aimed to assess the impact of coeliac axis stenosis on outcomes after oesophagectomy for cancer. Methods: The study included consecutive patients who had an Ivor Lewis procedure with curative intent for middle‐ and lower‐third oesophageal cancer at two tertiary referral centres. All patients underwent preoperative multidetector CT with arterial phase to detect coeliac axis stenosis. The coeliac artery was classified as normal, with extrinsic stenosis due to a median arcuate ligament or with intrinsic stenosis caused by atherosclerosis. Results: Some 481 patients underwent an Ivor Lewis procedure. Of these, ten (2·1 per cent) developed oesophageal conduit necrosis after surgery. Coeliac artery evaluation revealed a completely normal artery in 431 patients (91·5 per cent) in the group without conduit necrosis and in one (10 per cent) with necrosis ( P < 0·001). Extrinsic stenosis of the coeliac artery due to a median arcuate ligament was found in two patients (0·4 per cent) without conduit necrosis and five (50 per cent) with necrosis ( P < 0·001). Intrinsic stenosis of the coeliac artery was found in 11 (2·3 per cent) and eight (80 per cent) patients respectively ( P < 0·001). Eight patients without (1·7 per cent) and five (50 per cent) with conduit necrosis had a single and thin left gastric artery ( P < 0·001). Conclusion: This study suggests that oesophageal conduit necrosis after oesophagectomy for cancer may be due to pre‐existing coeliac axis stenosis. Abstract : Vascular abnormalities may be causal